'Techno-eco-efficiency' performance of 3D printed impellers: an application of life cycle assessment. (30th July 2021) - Jayawardane, Heshan; Davies, Ian J.; Leadbeater, Garry; John, Michele; Biswas, Wahidul K.
Rapid industrialisation had led to a scarcity of resources. The concept of sustainable manufacturing has emerged to address this scarcity and to minimise environmental degradation. 3D printing also known as additive manufacturing, could potentially reduce material wastage, energy consumption and resulting emissions. A 'techno-eco-efficiency' framework was developed to produce technically, economically, and environmentally feasible centrifugal pump impellers 3D printed using the fused filament fabrication process. Firstly, surface properties, geometric properties, build material properties, static structural and dynamic properties, and the hydraulic performance of impellers were assessed in order to investigate how process parameters, such as infill pattern, infill rate and reinforcement material affect the technical performance. Secondly, the eco-efficiency performance of technically suitable impellers was assessed using environmental life cycle assessment, life cycle costing tools and portfolio analysis. Thus, this 'techno-eco-efficiency' framework was used to achieve sustainable manufacturing and could act as a decision support tool for selecting cost-competitive, environmentally benign, and technically feasible products. Alternatively, it would assist product designers and manufacturers to minimise a trade-off between technical and resulting eco-efficiency performance.